Fine-tuned MOF-74 type variants with open metal sites for high volumetric hydrogen storage at near-ambient temperature - Kim, Dae Won; Jung, Minji; Shin, Dong Yun; Kim, Namju; Park, Jaewoo; Lee, Jung-Hoon; Oh, Hyunchul; Hong, Chang Seop (Elsevier BV, 2024)
Adsorbent-based hydrogen storage systems offer a potential solution to current challenges in hydrogen storage, particularly those requiring high pressures or cryogenic temperatures. Specifically, the use of metal-organic frameworks (MOFs) featuring open metal sites that strongly adsorb hydrogen represents a promising strategy for near-ambient-temperature hydrogen storage. This study investigates the hydrogen storage properties of M2(dondc) (M = Mg2+, Co2+, and Ni2+), an extended version of MOF-74. Among this series, Ni2(dondc) exhibits the second-highest volumetric hydrogen capacity of 10.74 g L-1 at 298 K under pressure swing adsorption conditions (100 to 5 bar) at ambient temperatures. The superior hydrogen storage performance of Ni2(dondc) is attributed to its highly polarizable Ni open metal sites and a significant heat of adsorption of 12.2 kJ mol- 1. These findings are corroborated by temperature-programmed desorption spectroscopy and van der Waalscorrected density functional theory calculations. In addition to its exceptional hydrogen capacity, Ni2(dondc) exhibits robust structural stability and long-term durability, positioning it as a promising candidate for nearambient-temperature hydrogen storage applications.